Oxytelus acriculiclypeatus, a New Species of Oxytelus Gravenhorst, 1802 (Coleoptera: Staphylinidae: Oxytelinae) from Borneo - Lü, Liang (Zootaxa, 2024)
A new species, Oxytelus acriculiclypeatus sp. nov., is described from Malaysia (Borneo: Sabah). The species is similar to O. megaceros Fauvel, 1895, but can be separated based on four male features: a more pointed tip on the anterior margin of the clypeus, a wider central plate on the posterior margin of sternite VIII with a carina that spans the entire width of the posterior margin of medial plate, two sharper and thinner projections on the apical orifice, and the apico-medial hook with a smaller apical tip but without the connecting scape. As a result, a total of 31 confirmed species have been recorded in Southeast Asia hitherto.